Transforaminal endoscopic lumbar foraminotomy for octogenarian patients - Ahn, Yong; Song, Sung-Kyu (Frontiers in Surgery, 2024)
Background: Radiculopathy caused by lumbar foraminal stenosis in older people has become more common in the aging general population. However, patients aged ≥80 years rarely undergo conventional open surgery under general anesthesia because of the high risk of peri-operative morbidity and adverse events. Therefore, less invasive surgical alternatives are needed for older or medically handicapped patients. Transforaminal endoscopic lumbar foraminotomy (TELF) under local anesthesia may be helpful in at-risk patients, although only limited information is available regarding the clinical outcomes of this procedure in octogenarians. Therefore, this study aimed to investigate the safety and efficacy of TELF for treating radiculopathy induced by foraminal stenosis in octogenarian patients. Methods: Overall, 32 consecutive octogenarian patients with lumbar foraminal stenosis underwent TELF between January 2019 and January 2021. The inclusion criterion was unilateral radiculopathy secondary to lumbar foraminal stenosis. The pain focus was confirmed using imaging studies and selective nerve blocks. Full-scale foraminal decompression was performed using a percutaneous transforaminal endoscopic approach under local anesthesia. Surgical outcomes were assessed using the visual analog pain score, Oswestry Disability Index, and modified MacNab criteria.Results: The pain scores and functional outcomes improved significantly during the 24-month follow-up period, and the rate of clinical improvement was 93.75% in 30 of the 32 patients. None of the patients experienced systemic complications.Conclusion: TELF under local anesthesia is an effective and safe treatment for foraminal stenosis in octogenarian or medically compromised patients. The mid-term follow-up did not reveal any significant progression in spinal stability. Therefore, this endoscopic procedure can be an effective alternative to aggressive surgery for managing lumbar foraminal stenosis in octogenarian patients with intractable radiculopathy.